THE COMPLEXITY OF READING COMPREHENSION PROCESSES: A REVIEW FROM READER, TEXT, AND COGNITIVE PROCESS PERSPECTIVES - Magdalena Br. Marpaung; Humiras Betty M. Sihombing (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2021)
This is a review of reading comprehension theories from published articles. This theoretical review differs its content by showing reading complexities which is viewed from the perspective of its readers, text’s, and cognitive process. Readers individual differences are highly affect reading comprehension process as it can be also the source of its complexity by the factors of attitude, habit, and linguistics proficiency (Cassanave: 1988, Mcmaster: K.L., Espin, C.A., Van den Broek: 2014). On the other side, texts as the mediator of reader and writer interaction in reading process as also play an important factor in turning reading to be complex process, genre, content, format, and degree of difficulty are sub-factors that affect the complexity of reading in readers mind (Mcmaster, K.L., Espin, C.S., Van den broek; 2014). However, as the motor of reading process, cognitive activities are also play its important role started from decoding, translation, schemata, questioning, and metacognition process are closely affect reading comprehension process. As mainly composed from published article, this review focus to articles which are published on the year of 2000 and above but for a better result of reviews this theoretical review is taken Cassanave research result which was published on 1988 and Van den Broek research result which was published on 1999.